2020
DOI: 10.2147/cmar.s257934
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Prognostic Value of Inflammation Factors in Hepatocellular Carcinoma Patients with Hepatic Artery Interventional Treatments: A Retrospective Study</p>

Abstract: Background: Hepatic artery interventional therapy has been recognized as the first choice for advanced liver cancer. However, reliable prognostic markers are still lacking. In the present study, we aimed to evaluate the prognostic value of inflammation factors including neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR) and monocyte to lymphocyte ratio (MLR) in hepatocellular carcinoma (HCC) patients with hepatic artery interventional treatments. Methods: Patients undergoing hepatic arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…AFR is a novel indicator reflecting inflammation and nutrition status [ 27 ], while NLR is reliably reflecting inflammation [ 28 ]. AFR and NLR were both widely used as prognostic indicators in various diseases [ 29 , 30 ]. These studies strongly suggest a close association between inflammation and POD.…”
Section: Discussionmentioning
confidence: 99%
“…AFR is a novel indicator reflecting inflammation and nutrition status [ 27 ], while NLR is reliably reflecting inflammation [ 28 ]. AFR and NLR were both widely used as prognostic indicators in various diseases [ 29 , 30 ]. These studies strongly suggest a close association between inflammation and POD.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the prediction model of prognosis of the HCC combined with different in ammation factors has always been a hot issue [9,10,29,30]. Previous studies have examined GLR's prognostic ability in HCC [14,31], intrahepatic cholangiocarcinoma [32] and nonfunctional pancreatic neuroendocrine tumors [25].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical observational studies have demonstrated that elevated neutrophil count and increased NLR are used as markers of advanced disease, poor prognosis and poor response to therapy in patients with HCC [11][12][13][14] . Nevertheless, when it comes to causal inference, observational studies may be biased by confounding factors and reverse causality.…”
Section: Introductionmentioning
confidence: 99%